(untitled) (Revista LIDER, 2020)
Development is always a vision, image or expectation of the future. However, in territories produced by mining extractivism, where the environmental conditions that allow or permitted certain ways of life are destroyed, that situation is signified by local communities as a breakdown of projections and possibilities for future developments. Through the study of different notions and conceptual perspectives on development and territory, past life conditions are identified that were re-signified to give meaning and content to the definition of development in the cases of the Aymara Community of Cancosa and in the town of Quillagua. We found that mining extractivism produced environmental damage that radically limits current and future development possibilities, causing its inhabitants to perceive that the environmental and social conditions they had in the past constitute the only imaginary of possible development.